Menata dan Mengelola Lembaga Pendidikan Yang Good Governance di Era Otonomi Daerah (Studi di Dinas Pendidikan Padang Sidempuan) - Nurhamidah Gajah; Muksana Pasaribu (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2023)
The current era of educational autonomy is a decisive moment in building a culture of regional education governance through the development of an effective educational planning system and good governance. The principle of regional autonomy is the widest possible autonomy in the sense that the region is given the authority to manage and regulate all government affairs outside of being the affairs of the regional government as stipulated in the applicable laws and regulations. The results of the study provide an overview of the Padang Sidempuan City Education Office having the authority to make regional policies in the framework of public services, increasing roles, initiatives, and community empowerment aimed at improving welfare and community services. towards education in the city of Padang Sidempuan. Practical education management in creating good governance. The arrangement and management of good governance educational institutions can be seen from the commitment of the education office to formulate the vision and mission of the institution. Leadership is quite visionary, developing the education sector, setting and fulfilling education quality standards in accordance with the expectations of stakeholders. Have strong political will accompanied by policies and planning systems that prioritize the importance of education as a human investment effort.